Separation performance of p-tert-butyl(tetradecyloxy)calix[6]arene as a stationary phase for capillary gas chromatography. Issue 66 (25th November 2019) - Sun, Tao; Shuai, Xiaomin; Chen, Yujie; Zhao, Xinyu; Song, Qianqian; Ren, Kaixin; Jiang, Xingxing; Hu, Shaoqiang; Cai, Zhiqiang
Abstract : This work presents the first example of the utilization of p-tert -butyl(tetradecyloxy)calix[6]arene (C6A-C10) as a stationary phase for capillary gas chromatographic (GC) separation. Abstract : This work presents the first example of the utilization of p-tert -butyl(tetradecyloxy)calix[6]arene (C6A-C10) as a stationary phase for capillary gas chromatographic (GC) separation. The statically coated C6A-C10 column showed a column efficiency of 3293 plates per m and had a nonpolar nature. Its selectivity and retention behaviour were investigated using a number of mixtures of diverse analytes and their isomers. As a result, the C6A-C10 column exhibited high resolving capability for aliphatic and aromatic analytes from apolar to polar nature, especially for positional, structural and cis -/ trans -isomers. Moreover, the C6A-C10 column showed thermal stability up to 240 °C. In addition, it was applied for the determination of isomer impurities in real samples, proving its good potential for practical GC analysis.